Flemingia sootepensis (Leguminosae): its occurrence in India, notes on identity and typification - Gavade, Sandip K.; van Der Maesen, L.j.g.; Lekhak, Manoj M. (Phytotaxa, 2017)
Flemingia sootepensis Craib (Leguminosae-Papilionoideae) has been collected from the Western Ghats. This paper is the first report of the species from India. In addition, the binomial F. sootepensis is lectotypified, and a detailed description and colour photos are provided to facilitate identification of this species.